(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2010)
Si recensisce Cristina Marras, Metaphora translata voce. Prospettive metaforiche nella filosofia di G. W. Leibniz, Leo S. Olschki Editore, Firenze, 2010.